Unjustified punishment: A recipe for failure in Egypt - Hanafy, Hend (AUC Knowledge Fountain, 2016)
Since the beginning of a new phase of governance in Egypt on the 3rd of July 2013, there has been a remarkable trend of using punishment as a mechanism for repression to control of the public realm in relation to protests, civil society organizations’ work,and political opposition dissent, especially regarding Muslim Brotherhood organization. This paper argues that such use of punishment though possibly successful in the short run is likely to fail in the long run. Such failure is due to the lack of moral and philosophical justifications of punishment, whether based on consequentialism or retributivism theories of punishment. Further, such unjustified punishment decreases the legitimacy of the Egyptian regime, thus increasing the likelihood of political instability and dissent.